Mental health symptoms and disorders in elite athletes: A systematic review - Guszkowska, M. (Acta Kinesiologica, 2025)
Purpose: Findings of recent reviews show that the prevalence of mental health symptoms and disorders among both current and former elite athletes appears to be substantial and similar to the prevalence in the general population. The aim of the current systematic review was to determine the prevalence of distress, anxiety and depression symptoms, sleep disorders, nutrition disorders, and substance use in elite active athletes.